2012
DOI: 10.1108/00012531211244770
|View full text |Cite
|
Sign up to set email alerts
|

A compound correlation model for disjoint literature‐based knowledge discovery

Abstract: Purpose -The algorithm of disjoint literature-based knowledge discovery provides a convenient, efficient and effective auxiliary method for scientific research. Based on an analysis of Swanson's A-B-C model of disjoint literature-based knowledge discovery and Gordon's intermediate literature theory, this paper seeks to propose a more comprehensive compound correlation model for disjoint literature-based knowledge discovery. Design/methodology/approach -A new algorithm of vector space model (VSM) based disjoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As for the mechanism of the millisecond spike bursts or narrow-band type III bursts, Benz (1986) proposed that decimeter narrow band millisecond spikes are coherent emission as a signature of electron acceleration in flare, and the flare energy release must be fragmented with each spike indicating a single energy release episode in the smallest time and space scale originated from magnetic reconnection sites (Huang & Nakajima 2005. Fleishman & Melnikov (1999) made a detailed comparison of the observed spike properties with various theoretical models, and found that the electron cyclotron maser emission (ECME) driven by nonthermal electrons can explain almost all the observed properties.…”
Section: Physical Discussionmentioning
confidence: 99%
“…As for the mechanism of the millisecond spike bursts or narrow-band type III bursts, Benz (1986) proposed that decimeter narrow band millisecond spikes are coherent emission as a signature of electron acceleration in flare, and the flare energy release must be fragmented with each spike indicating a single energy release episode in the smallest time and space scale originated from magnetic reconnection sites (Huang & Nakajima 2005. Fleishman & Melnikov (1999) made a detailed comparison of the observed spike properties with various theoretical models, and found that the electron cyclotron maser emission (ECME) driven by nonthermal electrons can explain almost all the observed properties.…”
Section: Physical Discussionmentioning
confidence: 99%
“…Most other applications were in the fields of innovation and technology management. For instance, Kostoff et al ( 2008 ) explored the applicability of LBD in finding technologies related to water purification, while Huang et al ( 2012 ) used a similar approach focused on agricultural economics. This involved the integration of text mining with network analysis in the works of technology management scholars.…”
Section: Introductionmentioning
confidence: 99%